Strengthening Coastal Community Empowerment in Lamungan Batu Village : Sustainable Environmental and Socio-Economic Solutions - Suwanti Suwanti; Iwan Adinugroho; Sudirman Sudirman (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study explores community empowerment initiatives in Lamungan Batu Village through a multidisciplinary approach integrating environmental sustainability, public health awareness, and participatory governance. The objective was to identify challenges and mobilize local capacities in addressing waste management, food security, and social issues such as stunting and early marriage. Using field observations, participatory action methods. Key findings show that combining health education, environmental campaigns, and youth led innovation fosters a stronger sense of ownership and behavior change within the community. This paper concludes that community based learning integrated into village development planning holds substantial potential for long term impact and can be replicated in other rural coastal areas undergoing similar socio environmental transitions.